Surface species of supported ruthenium catalysts in selective hydrogenation of levulinic esters for bio-refinery application - Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V. (Catalysis Letters, 2012)
Several supported noble metal catalysts were screened for the hydrogenation of methyl levulinate to gamma-valerolactone (GVL). Among these catalysts 5 % Ru/C showed the highest conversion of 95 % of methyl levulinate with 91 % selectivity to GVL. A detailed characterization was carried out using TPR, XRD, XPS and BET techniques. XPS studies revealed that higher extent of Ru-0 species in case of carbon supported Ru was responsible for its higher hydrogenation activity as compared to Ru on other supports. Effect of process parameters such as temperature, H-2 pressure, catalyst and substrate concentration and metal loading on methyl LA conversion and selectivity to GVL also has been studied. 5 % Ru/C catalyst was found to be stable up to five reuses.
Keywords: 5 % Ru/C; Biofeedstock; gamma-Valerolactone; H-2-TPR; Hydrogenation; Methyl levulinate; XPS

Efficient synthesis of gamma-valerolactone-a potential fuel from biomass derived levulinic acid using catalytic transfer hydrogenation over Hf@CCSO3H catalyst - Jori, Popat K.; Jadhav, Vrushali H. (Catalysis Letters, 2020)
A new hafnium based carbonaceous catalyst (Hf@CCSO3H) was prepared by simultaneous carbonization and sulfonation of readily available glucose, followed by incorporation of hafnium metal on the surface of catalyst. The catalyst was well characterized using FT-IR, PXRD, EDX, SEM, C-13 CPNMR, XPS and BET analysis. The catalytic activity of Hf@CCSO3H was evaluated for synthesis of gamma-valerolactone-a potential fuel and green solvent. gamma-valerolactone was synthesized from biomass derived levulinic acid by catalytic transfer hydrogenation using 150 wt% of catalyst at 200 celcius for 24 h in isopropanol solvent as a hydrogen donor. 100% conversion of levulinic acid was achieved with an excellent yield of 96% with more than 99% selectivity of gamma-valerolactone as evident from GC analysis. The method developed is simple, efficient and economical. [GRAPHICS] .
Keywords: gamma-Valerolactone; Hydrogenation; levulinic acid; Transfer